Do We Need Supplements? - Puspitasari, Arina Dery; Samirah, Samirah; Asmad, Asma; Widyasari, Sekar Arum; Afrilla, Dian; Hakim, Lukman Nul; Mawaddah, Midfa'ul Haawan Fitayaatin; Leliga, Fenny Kusuma; Yusfar, Yunarti; Oktavia, Maria (Universitas Malahayati, 2025)
ABSTRACT Dietary supplements are produced in capsules, tablets, pills, and other similar forms, which are designed to be consumed as a dietary supplement. Most people today are aware of the role of nutrition in health, and they take supplements to improve the quality of their health, prevent diseases, supplement their diet, and boost their immunity. This study aims to analyze the knowledge of pharmacy students throughout Indonesia regarding the correct use of supplements. This study uses descriptive studies and administration of study instruments with a cross-sectional approach. The study instrument was a questionnaire with 10 questions. This study was conducted at Tanjung Pura University Pontianak in September 2023. The sampling method was random sampling with an accidental sampling technique. The number of samples collected for this study was 140 respondents. Almost all respondents had taken supplements, (99%; n=138). Based on the knowledge assessment score obtained through the questionnaire, it was found that 87% of pharmacy students throughout Indonesia had good knowledge of the correct selection and use of supplements and as many as 13% of students had poor knowledge of the correct selection and use of supplements. As many as 87% of respondents already knew about how to choose/use supplements correctly. Keywords: Supplement, Nutrition, Multivitamin, Mineral